Durian volume determination using short-range coded-light three-dimensional scanner - Cheepsomsong, Thana; Siriphanich, Jingtair (Agriculture and Natural Resources, 2022)
Importance of the work: The quality of a durian fruit can be inferred from its specific gravity, whose determination requires its volume. Traditionally, the volume of a durian is determined by the water displacement method; However, this is a slow process that runs the risk of fungal growth due to residual high humidity. Objectives: The present study evaluated the viability of three-dimensional (3D) scanning as an alternative approach to water displacement for the determination of the volume of durian fruit. Materials & Methods: Durian fruit samples at different maturity levels and harvested from two different growing areas were determined for volume using the traditional specific gravity method and compared with volumes measured using the 3D scanning method. Each scan took about 60 s. Results: The analysis showed that there was no significant (p > 0.05) difference between the traditional and proposed methods for durian fruit of different maturity levels. The average relative percentage difference was 1.06% (sample size of 116), which was less than that obtained from other reported studies that tested other fruits with reasonable axial symmetry. Main finding: The proposed alternative technique has potential for the continuous and automatic measurement of the volumes of durian fruit on a moving conveyor belt, as a part of the maturity determination process.